The clinical effects of high-frequency oscillatory ventilation in the treatment of neonatal severe meconium aspiration syndrome complicated with severe acute respiratory distress syndrome - Guang Yang; Yunxia Qiao; Xinxin Sun; Tiandan Yang; Aiying Lv; Min Deng (BMC, 2021)
Abstract Objective To explore the efficacy and safety of high-frequency oscillatory ventilation (HFOV) in the treatment of severe meconium aspiration syndrome (MAS) complicated with severe acute respiratory distress syndrome (ARDS). Methods A total of 65 infants with severe MAS complicated with severe ARDS were included in the study. The clinical efficacy of treatment for the HFOV group (n = 31) and the conventional mechanical ventilation (CMV) group (n = 34) was retrospectively analysed. The partial pressure of oxygen (PaO2), partial pressure of carbon dioxide (PaCO2), PaO2/fraction of inspired oxygen (FiO2), and oxygen index values before and at 6, 12, 24, 48, and 72 h after mechanical ventilation, the mechanical ventilation time, oxygen inhalation time, incidence of complications, and outcomes of the two groups were compared. Results At 6, 12, 24, and 48 h after mechanical ventilation, the PaO2 in the HFOV group was significantly higher than in the CMV group, while the PaCO2 in the HFOV group was significantly lower than in the CMV group (P < 0.05). At 6, 12, 24, 48, and 72 h after mechanical ventilation, PaO2/FiO2 in the HFOV group was significantly higher than in the CMV group, and the OI in the HFOV group was significantly lower than in the CMV group (P < 0.05). Mechanical ventilation time, oxygen inhalation time, and the incidence of air leakage were significantly lower in the HFOV than in the CMV group (P < 0.05). Conclusions Overall, HFOV can effectively improve lung ventilation and oxygenation function, shorten ventilator treatment time, and reduce the incidence rate of air leakage for neonatal MAS, making it a safe and effective treatment option.